The Role of Motivation in the English Language Growth of International Students After University Entry - Dooey, Patricia; Oliver, Rhonda; Rochecouste, J. (English Australia, 2012)
Many international students from culturally and linguistically diverse backgrounds undertake tertiary studies in Australian universities. Academic success is dependent, at least in part, on English language proficiency, and students need to be motivated to improve their language ability over a prolonged period throughout the course of their degree. The study reported in this article aimed to assess the role of motivation in improving the English language proficiency of international students. The sample, taken from five universities in Australia, included undergraduate and postgraduate (coursework and research) students. Both quantitative and qualitative data were gathered, using surveys and interviews. Results indicate that while the importance of English language is acknowledged, international students frequently encounter barriers which impede their motivation to improve. It is recommended that universities provide adequate ongoing support to sustain students’ motivation in order to improve student retention rates and to produce the desired graduate skills.